Design and optimisation of vehicle frontal bumper beam with alternative carbon fibre-reinforced plastics in corrugated sandwich structure. Issue 6 (2nd November 2022) - Li, Mingzhi; Sang, Lin; Xiong, Zhihua; Hou, Wenbin
Abstract: Bumper beam is the key structure to protect the vehicle from impact collision. The aim of this paper is to propose a novel bumper beam consisting of continuous carbon fibre-reinforced plastic (CFRP) bumper beam, which is assembled by carbon fibre-reinforced epoxy (EP/CF) skin panels and carbon fibre-reinforced polycarbonate (PC/CF) corrugated sandwich cores. First, the proposed bumper structure is compression molded and then the crashworthiness performance is evaluated via impact experimental test and numerical analysis. It is demonstrated that the numerical results are in good agreement with the experimental data. Then, the effect of the thickness of panel and core on the intrusion, impact force and specific absorption on the impact performance is investigated by using the sensitivity analysis. Based on this, the Kriging proxy model is adopted for design of experiment (DOE), and a multi-objective optimisation with NSGA-II genetic algorithm is used to optimise the thickness (layers) of the skin panels and sandwich core. Results show that the impact performance meet the requirement of crashworthiness with a mass reduce of 35.57%. Accordingly, the proposed bumper beam exhibit superior impact performance, reduced weight to the traditional integrated counterpart. Furthermore, the structure-material-performance integration is an effective method to design CFRP as structural parts.